HISTORICAL AND PEDAGOGICAL CHARACTERISTICS OF THE IDEAS OF SPIRITUAL AND MORAL EDUCATION IN KAYKOVUS’S “QABUSNAMA” (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the historical and pedagogical characteristics of the ideas of spiritual and moral education presented in Kaykovus’s Qabusnama. The study interprets the work as an important source of Eastern didactic thought that integrates ethical instruction, social experience, educational guidance, and practical norms of human conduct. Special attention is paid to the historical context of the work, its place within the tradition of advice literature, and its significance in the formation of moral qualities such as honesty, modesty, diligence, justice, responsibility, respect for parents, and reverence for knowledge. The article argues that Qabusnama should be understood not only as a literary and moral monument of the eleventh century but also as a pedagogical text containing systematic views on the upbringing of the younger generation. Using historical-pedagogical interpretation, the paper reveals that Kaykovus connected moral maturity with intellectual discipline, speech culture, labor education, and social behavior. The work also demonstrates that the author approached education as a lifelong process grounded in self-control, ethical awareness, and the harmonious development of personality. From the standpoint of contemporary pedagogy, the ideas expressed in Qabusnama retain methodological value for the moral education of students, especially in the context of strengthening national heritage, cultural continuity, and value-oriented education in teacher preparation. The article concludes that the educational potential of the work lies in its synthesis of moral advice, social responsibility, and practical wisdom, which makes it relevant for modern pedagogical reflection. The interpretation is grounded in source material discussing the work’s didactic orientation, its chapters on knowledge, conduct, labor, and upbringing, and its continued pedagogical significance.
Keywords: Qabusnama, Kaykovus, spiritual and moral education, historical pedagogy, Eastern didactics, moral upbringing, ethical values, advice literature.